Institutional Quality and Foreign Direct Investment Inflows: The Case of Vietnam - Minh, Cao Hong (Asian Economic and Financial Review, 2019)
This article examines the effect of institutional quality on Foreign Direct Investment (FDI) inflows in Vietnam, using a set of panel data from a Provincial Competitiveness Index (PCI) survey and inward FDI to 59 provinces and cities of Vietnam in the period of 2010-2017. This study also accounts for the fundamental determinants of FDI and gravity variables that are widely used in studies of FDI. In order to tackle the problem of endogeneity including reverse causality, a very classic problem facing almost the researches on determinants of FDI, this study applies Difference Generalize Method of Moments (GMM) estimation with period-specific predetermined instruments to investigate the relation between quality of provincial governance and FDI inflows. After controlling for factors other than institutional quality, the outcome shows that the provincial competitiveness index in terms of institutional quality is significant in explaining the difference in inward FDI from province to province in Vietnam.